Efficient MAC Based AODV Routing Protocol to improve the efficiency of MANET - Rajeshkanna, R.; .Saradha, DrA (IJRDO -Journal of Computer Science Engineering, 2015)
Currently, multimedia and real-time applications use much network resources and so, need high flow rates and very small transfer delay. The present ad hoc networks , in their original state, are not able to satisfy the requirements of quality of service (QoS). Researches for improving QoS in these networks are main topics and a subject of intensive researches. In Adhoc networks, the routing phase plays an important role for improving QoS. Numerous routing protocols (proactive, reactive and hybrid) were proposed. AODV (Adhoc On demand Distance Vector) is probably the more treated in literature In this article, we propose a new variant based on the AODV which gives better results than the original AODV protocol with respect of a set of QoS parameters and under different constraints, taking into account the limited resources of mobile environments (bandwidth, energy, etc…). The proposed variant (EMAODV) suggests that the discovering operation for paths reconstruction should be done from the source. It also defines a new mechanism for determining multiple disjoint routes.